Severe Myositis, Myocarditis, and Myasthenia Gravis with Elevated Anti-Striated Muscle Antibody following Single Dose of Ipilimumab-Nivolumab Therapy in a Patient with Metastatic Melanoma - Mahdieh Fazel; Patrick M. Jedlowski (Case Reports in Immunology)
Immune checkpoint inhibitors targeting programmed cell death protein 1 and cytotoxic T-lymphocyte associated protein 4 have improved survival in patients with metastatic melanoma, especially in combination (i.e., ipilimumab-nivolumab). Postmarketing surveillance has identified rare but at times life-threatening adverse effects associated with these agents in combination and as monotherapy, which include myocarditis, myositis, myasthenia gravis (MG), and hepatotoxicity. Further evaluation of immune checkpoint therapy-induced MG identified the rapid clinical progression, prolonged treatment/supportive therapy course, and higher frequency of myasthenic crisis in these patients versus those with idiopathic MG. More rapid incorporation of aggressive treatment options (i.e., intravenous immunoglobulin, plasmapheresis) may be necessary in these cases. Anti-striational antibodies are often detected in individuals with myasthenia gravis and concurrent myositis and myocarditis. A high-index of suspicion is necessary to assist with rapid treatment initiation as these patients can rapidly deteriorate into respiratory compromise. A case of a 78-year-old woman with metastatic melanoma status after combination therapy with ipilimumab-nivolumab that developed transaminitis, myositis, myocarditis, and myasthenia gravis (with positive anti-striational antibodies) five days after the first cycle, is presented. Despite high dose intravenous methylprednisolone and intravenous immunoglobulin treatment, she ultimately entered hospice care eight days after hospital admission, 36 days after her first cycle.